2003
DOI: 10.1016/s1010-7940(03)00270-7
|View full text |Cite
|
Sign up to set email alerts
|

Intramural hematoma and dissection involving ascending aorta: the clinical features and prognosis

Abstract: Type A IMH tends to occur in older, more hypertensive and not hyperlipidemic patients, showed lower incidences of preoperative aortic valve regurgitation and pericardial effusion than dissection. Medical treatment alone was not enough to manage all type A IMH patients, and 47.2% (17/36) of the patients needed surgical intervention. Urgent surgical repair was not necessary for all type A IMH patients to achieve favorable surgical outcome with careful follow-up using imaging modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 13 publications
2
26
2
Order By: Relevance
“…A similar conclusion was reached by Song et al (9). The average age of patients presenting with intramural hematoma ranged from 58 to 71 years (median age: 68 years) (2,8,(10)(11)(12)(13)(14)(15), which is much older than the average of patients with classic AD (median age: 61 years) (16). The prevalence of Marfan syndrome is significantly lower in patients with intramural hematoma (9).…”
Section: Imh: a Precursor To Classic Dissection Or A Distinct Diseasesupporting
confidence: 62%
“…A similar conclusion was reached by Song et al (9). The average age of patients presenting with intramural hematoma ranged from 58 to 71 years (median age: 68 years) (2,8,(10)(11)(12)(13)(14)(15), which is much older than the average of patients with classic AD (median age: 61 years) (16). The prevalence of Marfan syndrome is significantly lower in patients with intramural hematoma (9).…”
Section: Imh: a Precursor To Classic Dissection Or A Distinct Diseasesupporting
confidence: 62%
“…Moreover, a delayed operation in the initial medical treatment group was not infrequently needed; the operative frequency was 32% (25/79) in our study, which is intermediate between the previously reported frequencies of 27% (7/26) and 43% (13/30). 5,19 These findings reinforce the importance of thorough analysis to characterize the clinical features of any adverse event and to seek valuable predictors of such occurrences.…”
Section: Adverse Events Without Urgent Surgery and Prognostic Role Ofmentioning
confidence: 74%
“…5,19 However, the temporal pattern and its prognostic impact have not been investigated in detail. In the present study, AD developed in a rather random fashion within 2 months from initial symptom onset, and the risk of AD development seems not to be critically time dependent.…”
Section: Adverse Events Without Urgent Surgery and Prognostic Role Ofmentioning
confidence: 99%
“…Our findings suggest the prognosis of type A IMH is not as benign as previously thought in Asian patients. Although prior Asian series 9 -11 have reported low death rates in type A IMH with medical therapy, a significant proportion [11][12][13] of patients (up to 50%) go on to develop serious complications and required urgent surgical intervention.…”
Section: Discussionmentioning
confidence: 95%